In vitro derived mouse A9 cell clones differing in malignancy: analysis by somatic cell hybridization with YACIR lymphoma cell clones. - Clements, G B (1976)
A culture of mouse A9 cells yielded clones of both high and low malignancy. Confirmation of the differences in malignancy of the clones was obtained after their hybridization with subclones of YACIR a lymphoma induced by Moloney leukemia virus. Low malignant A9 clones suppressed the malignancy of the YACIR partner in the hybrids. Hybrids between a highly malignant A9 cline and two different clones of YACIR "complemented" to yield hybrids of reduced malignancy. No correlation was formed between the malignancy of a particular A9 clone and its ability to produce a focus-forming mouse C-type virus.